Lúdico e a matemática: a utilização dos jogos para aprendizagem de operações matemáticas nos anos iniciais do ensino fundamental - Lima, Nádima Rosa Marques (Brasil, 2023)
This scientific study aims to analyze the impacts of the use of ludic activities and games in the teaching of mathematics in the early years, considering the motivational, cognitive and affective aspects of students. The research is based on previous studies that highlight the importance of play in children's cognitive development and mathematical learning. Recent research shows that recreational activities promote greater engagement, understanding of concepts and application of mathematical algorithms. In addition, the playful approach favors the development of socio-emotional skills such as collaboration, communication and mutual respect. The book "Fun Mathematics: Games and Play for Elementary Education" is presented as a reference that offers playful activities to be used in the classroom. The methodology proposed for the research involves the use of games, games and the number line as pedagogical resources. The analysis of the results indicates that the use of the number line is an effective tool in teaching addition and subtraction operations in the early years, promoting understanding of concepts and development of logical-mathematical thinking. The article concludes that ludic strategies and games have the potential to improve the quality of mathematics teaching, providing more attractive, meaningful and enjoyable learning for students. It is suggested that future research explore other playful strategies and assess their impacts on different aspects of mathematical learning.